ADOPTING TRIPLE BOTTOM LINE APPROACH: TRANSFORMATIVE STRATEGIES FOR SUSTAINABLE MANAGEMENT AND ACCOUNTING - Ratiyah, Ratiyah; Bahri, Syamsul; Hartanti, Hartanti (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The adoption of the Triple Bottom Line (TBL) approach has gained momentum as organizations seek to integrate social, environmental, and economic considerations into their decision-making processes. This paper aims to explore transformative strategies for sustainable management and accounting through the implementation of the TBL approach. The research objectives include examining the challenges and opportunities associated with adopting TBL, analyzing the impact on organizational practices, and identifying key success factors. A qualitative research method is employed, incorporating case studies and interviews with practitioners. Findings reveal that organizations face various challenges in implementing TBL, including measurement difficulties and resistance to change. However, successful adoption of TBL can lead to enhanced stakeholder engagement, improved resource efficiency, and long-term financial viability. This paper contributes to the literature by providing insights into the practical implications of adopting TBL for sustainable management and accounting practices.